Essential Readings in e-Science - Kathy Szigeti; Kathy Wheeler (Issues in Science and Technology Librarianship)
The amount of data that scientists produce continues to increase every year. People are needed to handle, preserve, describe, and organize that data, and, because many of these tasks are similar to what librarians have done with publications for centuries, it makes sense that librarians would have a role in the emerging task of managing scientific data. It is the purpose of this paper to give librarians a core set of readings to turn to in order to begin learning about this new task in our field; to help us, as individuals and as a profession, understand what our roles will be in the area of "e-Science." [ABSTRACT FROM AUTHOR]